G20: Participation of Non-State Actors and Prospects for the Brazilian Presidency - Loureiro, Márcia (CEBRI-Revista: Brazilian Journal of International Affairs, 2024)
This article focuses on the role of non-state actors in the G20 structure, through their participation in the Engagement Groups. It outlines how these groups have evolved and what to expect in 2024, concerning the degree of convergence between their agendas and the priorities of the Brazilian Presidency, and the possible improvement of government-society interaction mechanisms. The article also discusses some challenges to the consolidation and meaningful participation of Engagement Groups in the G20 processes.